Origin of the Lancasterian school in Colombia: historiography and purpose of implementation in the Cúcuta Constitution of 1821. - Acevedo Tarazona, Álvaro; Villamizar Palacios, Carlos (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2024)
Objective: This article analyzes the adoption and implementation difficulties of the Lancasterian method in the nascent Colombia of 1821, which at the time consisted of present-day Colombia, Ecuador and Venezuela. Originality/aims: It seeks to explain the difficulties of implementation of the method in the light of its context and in a comparative relation with the experience in other countries. Method: The Lancasterian method promulgated in the Constitution of Villa del Rosario de Cúcuta, which was born as the most important milestone of compulsory schooling in Latin America, is analyzed in the light of the context of the Enlightenment and its republican political interpretation in the continent, by means of the review of published and documentary sources. Strategies/information collection: The collection of information was carried out through documentary review of online sources, press and archival review, together with a bibliographic search of what has been published on the subject. Conclusions: When considering the intentions of the legislators to enact an educating State and the difficulties in the implementation of the Lancasterian method in Colombia in 1821, regarding other implementation experiences in Mexico and Peru, it was evident the failure due to the weakness of the nascent Colombian State itself and the constant wars and political instability.